A Study on the Challenges Faced by the Hotel and Startagies to Overcome them Post Covid-19 (Global Journal of Management and Business Research, 2022)
We heard information on Coronavirus and its adverse effects on the hotel industry. Yet, earlier, the hotel industry had to deal with numerous crises and viruses. In 2003, for instance, the SARS virus affected the industry. There was a 50 percent fall in hotel bookings, leading to a decrease in international tourist arrivals of almost 9.4 million, with losses between $30 billion and $50 billion. Despite the above-mentioned facts, by 2006, the travel industry was able to recover and report immense growth, with a total contribution of $5.160 billion to global GDP the same year. The papers reviewed concentrated on various aspects of the hotel industry, including the problems of hospitality workers, job loss, income impact, COVID-19 spreading Industry trends, consumer demand, prospects for hospitality industry recovery, safety and fitness, travel activity, and consumer choice
Keywords: COVID-19 pandemic; hospitality industry; challenges; strategies